Model Persamaan Struktural Faktor-Faktor yang Mempengaruhi Niat Kewirausahaan Mahasiswa FMIPA UNSRI - Dwipurwani, Oki (Jurnal Matematika; Vol 5 No 1 (2015)DO - 10.24843/JMAT.2015.v05.i01.p56, 2015)
The aim of this research is to know factors having an influence by significant to Entrepreneurship Intention of students in Faculty of Mathematics and Natural Sciences of Sriwijaya University. There used a Structural Equation Models (SEM) analysis method, because variables in this research in the form of laten variable and causal relationship between a set of variables nor modestly, there is direct and indirectly relationship. The result show that family environment give a part important in forming Entrepreneurship intention student, and so Personal attitude give biggest direct influence to Entrepreneurship Intention of student equal to 0,52 with t-test statistical value equal to 6,82.
Keywords: Structural Equation Models (SEM), Enterpreneurship Intentions, Kewirausahaan